Role of Manipulative Materials in Mathematics Teaching and Learning - Gnawali, Yagya Prasad (Education and Development, 2025)
This study explores how using manipulative materials affects mathematics teaching and learning in grade seven of basic schools. A qualitative approach with an ethnographic design was used, focusing on three basic schools in Kathmandu. The research included three grade-seven mathematics teachers and six students from three schools, selected through probability sampling. Semi-structured interviews were conducted to gather participants' views, and the validity of the interview guidelines was confirmed through expert review. I observed the mathematics classroom and conducted a focus group discussion with students. Data collection took place during the participants' classroom time and focus group discussion were conducted in students’ break time. Manipulative materials enhance problem-solving skills, build confidence, support different learning styles, and help teachers explain complex ideas effectively, making lessons fun and interactive. The findings show that manipulative materials greatly improve student engagement in mathematics, offering valuable insights for teachers and policymakers to enhance basic-level mathematics education.